Financialization and idealization. an analysis of the technical defense of the individual capitalization - Muñoz Ferrer, Álvaro (Revista Ethika+, 2020)
This paper aims to offer a philosophical analysis of the technical argument that is usually used to defend the Chilean individual capitalization system. It will be shown that, behind the technical discursiveness, two intimately connected issues remain hidden and we will seek to unveil them: the existence of highly idealized assumptions and the relationship between financialization, privatization of social security, and precariousness of the labor market. The paper proceeds as follows: first, we will show the role of the privatization of the pension system in the process of financialization of the Chilean economy. Second, we will address the relationship between financialization and precariousness of the labor market. Third, we will show the problem of idealization present in the technical argumentation of defense of the AFP system. Finally, we will make us of the Foucauldian notion of the veridiction regime to explain the reason for the validity of the technical argument.